Circadian clock gene BMAL1 controls testosterone production by regulating steroidogenesis‐related gene transcription in goat Leydig cells. Issue 9 (17th February 2021) - Xiao, Yaoyao; Zhao, Lijia; Li, Weidong; Wang, Xiaoyu; Ma, Tiantian; Yang, Luda; Gao, Lei; Li, Cuimei; Zhang, Manhui; Yang, Dan; Zhang, Jing; Jiang, Haizhen; et al.
Abstract: Testosterone is produced by Leydig cells (LCs) and undergoes diurnal changes in serum levels in rats, mice, and humans, but little is known in goats. The present study revealed that goat serum testosterone levels displayed diurnal rhythmic changes (peak time at ZT11.2). Immunohistochemical staining showed that BMAL1, a circadian clock protein, is highly expressed in goat LCs. ELISA revealed that both hCG (0–5 IU/ml) and 22R‐OH‐cholesterol (0–30 μM) addition stimulated testosterone synthesis in primary goat LCs in a dose‐dependent manner. Treating goat LCs with hCG (5 IU/ml) significantly increased intracellular cAMP levels. Additionally, real‐time quantitative polymerase chain reaction (PCR) analysis revealed that the circadian clock ( BMAL1, PER1, PER2, DBP, and NR1D1 ) and steroidogenesis‐related genes ( SF1, NUR77, StAR, HSD3B2, CYP17A1, CYP11A1, and HSD17B3 ) showed rhythmic expression patterns in goat LCs following dexamethasone synchronization. Several Bmal1‐Luc circadian oscillations were clearly observed in dexamethasone‐treated goat LCs transfected with the pLV6‐ Bmal1 ‐ Luc plasmid. BMAL1 knockdown significantly downregulated mRNA levels of PER2, NR1D1, DBP, StAR, HSD3B2, SF1, NUR77, and GATA4, and dramatically decreased StAR and HSD3B2 protein levels and testosterone production. In contrast, BMAL1 overexpression significantly increased the mRNA and protein expression levels of StAR and HSD17B3 and enhanced testosterone production. Reporter assays revealed that goat BMAL1, or in combination with mouse CLOCK, activated goat HSD17B3 transcription in vitro. These data indicate that BMAL1 contributes to testosterone production by regulating transcription of steroidogenesis‐related genes in goat LCs, providing a basis for further exploring the underlying mechanism by which the circadian clock regulates ruminant reproductive capability. Abstract : Serum testosterone levels in goats exhibit a diurnal rhythmic change, with high levels at ZT13, and low levels at ZT1. Knockdown of BMAL1 not only downregulates the expression levels of steroidogenesis‐related genes at both the mRNA and protein levels but also reduces the secretion of testosterone. In contrast, BMAL1 overexpression significantly increased the expression of steroidogenesis‐related genes and consistently enhanced testosterone production in goat LCs.